Analisis Hubungan Motivasi Belajar Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMK Al Ma’sum Stabat - Ahmad Affan Alhammam; Fajar Fadillah; Muhammad Abdullah Sani (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
If someone has intrinsic motivation within themselves, then they will consciously carry out an activity that does not require external motivation. In learning activities, intrinsic motivation is very necessary, especially in learning alone. It is very difficult for someone who does not have internal motivation to carry out continuous learning activities. This research is quantitative research because in it there is a process of finding knowledge by using data in the form of numbers as a tool to find information about what you want to know. This research collects data or objective information in the field regarding the relationship between motivation and learning achievement in Islamic religious education. There is a Significant Positive Relationship: The results of the analysis may show that there is a significant positive relationship between students' level of learning motivation and their learning achievement in Islamic Religious Education subjects. This means that the higher the students' learning motivation, the better their learning achievements in this subject.You can summarize the research findings, practical implications, and relevance of the results to education at SMK Al Ma''sum Stabat. You can also emphasize the importance of learning motivation in improving student learning achievement in Islamic Religious Education subjects.